In-situ generation of H2O2 in heterogeneous Fenton-like process with Fe/Ni bimetallic particle for Metronidazole degradation - Yildiz, Burcin; Yucel, Ahmet; Hanay, Ozge (Taylor & Francis Inc, 2022)
A microscale Fe/Ni bimetallic particle was examined to convert O-2 to H2O2 and further to center dot OH radicals and to degrade metronidazole (MNZ) antibiotic in a heterogeneous Fenton-like reaction. The properties of the bimetallic particle before and after the reaction were studied using SEM, EDX, XRD, and BET techniques. The complete removal of MNZ was achieved within 15 min with an initial pH of 3, oxygen flow rate of 150 L/h, Fe/Ni of 1 g/L, and MNZ of 25 mg/L. Under these conditions, the maximum H2O2 concentration of about 31 mg/L was generated but only 27% of TOC was removed after 60 min. The presence of NaCl and the high ionic strength accelerated the iron dissolution and MNZ removal efficiency. The reaction was mainly inhibited at the solution pH of 7, implying the significance of solution pH in Fenton-like process. Besides, the possible MNZ degradation pathway was further proposed based on the intermediates identified by GC/MS. Acetamide was monitored as the degradation intermediate. The results showed a significant contribution on the usage of a catalyst for in-situ generation of H2O2 via the activation of dissolved oxygen.
Keywords: Heterogeneous Fenton process; Metronidazole; Fe; Ni bimetallic particle; antibiotics removal